GAYA HIDUP, WORK-LIFE BALANCE, INTERNAL LOCUS OF CONTROL TERHADAP KINERJA MAHASISWA PEKERJA PART-TIME DI KOTA DENPASAR - I Gst Ayu Wirati Adriati; I Gusti Ayu Rika Damayanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
This study aims to analyze the effect of lifestyle, work-life balance and internal locus of control on the performance of part-time student workers in Denpasar City. The sample of this study consisted of 84 part-time working students in Denpasar City. Data collection was carried out by distributing questionnaires via a Google form using a Likert scale. The data was processed using multiple linear regression analysis method through SPSS 22. The results showed that lifestyle, work-life balance, and internal locus of control variables on performance obtained an F-count of 31.310 with a significance value of 0.000 (<0.05 ), which means lifestyle, work-life balance, internal locus of control simultaneously have a significant effect on the performance of part-time work students. In addition, the results of the t-test of the lifestyle variable stated a t-count value of 3.852, a work-life balance variable of 3.083 and an internal locus of control variable of 2.123 with a significance of 0.000 (<0.05), which means lifestyle, work -life balance and internal locus of control have a positive and significant partial effect on the performance of part-time student workers.